Harmonic feedback - Kelly, Tara. (New York : Henry Holt, 2010)
When Drea and her mother move in with her grandmother in Bellingham, Washington, the sixteen-year-old finds finds that she can have real friends, in spite of her Asperger's, and that even when you love someone it does not make life perfect.
Keywords: Emotional problems -- Fiction; Asperger's syndrome -- Fiction; Drug abuse -- Fiction; Rock music -- Fiction; Self-perception -- Fiction; Bellingham (Wash.) -- Fiction